URBAN DESIGN, INSTITUTIONAL CONTEXT AND DECISION-MAKING PROCESS. TWO CASES OF WATERFRONT REGENERATION IN APULIA (ITALY) - Attardi, Raffaele; Canta, Antonietta; Torre, Carmelo Maria (BDC. Bollettino Del Centro Calza Bini, 2014)
The procedures for the assignment of design tasks for urban transformation plans distinguish between direct assignment and public competition. The paper examines two case studies of waterfront regeneration in Apulia Region (Italy) which are characterized by two different procedures for the assignment of design tasks. A set of criteria for a multidimensional assessment of the urban transformation processes is defined, in order to understand to which extent the quality of the decision-making process – including the assignment of design tasks – can be a guarantee for the increase of the “complex social value” of the coastline, as an element of local identity for Italian port cities. Keywords: design task assignment, decision-making processes, waterfront regeneration